2015
DOI: 10.1007/s00406-015-0643-8
|View full text |Cite
|
Sign up to set email alerts
|

Tcf4 transgenic female mice display delayed adaptation in an auditory latent inhibition paradigm

Abstract: Schizophrenia (SZ) is a severe mental disorder affecting about 1 % of the human population. Patients show severe deficits in cognitive processing often characterized by an improper filtering of environmental stimuli. Independent genome-wide association studies confirmed a number of risk variants for SZ including several associated with the gene encoding the transcription factor 4 (TCF4). TCF4 is widely expressed in the central nervous system of mice and humans and seems to be important for brain development. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In animal models, it was demonstrated that overexpression of TCF4 in mice resulted in sensorimotor and fear conditioning impairments, highlighting the relevance of TCF4 in cognitive processes (Brzózka et al, 2010, 2016; Brzózka & Rossner, 2013). Analysis of Tcf4 polymorphisms in humans with schizophrenia confirmed the influence of this TF in processes like verbal declarative memory (Lennertz et al, 2011), attention‐related tasks (Zhu et al, 2013), problem‐solving tasks (Albanna et al, 2014), and lower cognitive performance (Hui et al, 2015).…”
Section: Ndd‐associated Multifactorial Disordersmentioning
confidence: 99%
“…In animal models, it was demonstrated that overexpression of TCF4 in mice resulted in sensorimotor and fear conditioning impairments, highlighting the relevance of TCF4 in cognitive processes (Brzózka et al, 2010, 2016; Brzózka & Rossner, 2013). Analysis of Tcf4 polymorphisms in humans with schizophrenia confirmed the influence of this TF in processes like verbal declarative memory (Lennertz et al, 2011), attention‐related tasks (Zhu et al, 2013), problem‐solving tasks (Albanna et al, 2014), and lower cognitive performance (Hui et al, 2015).…”
Section: Ndd‐associated Multifactorial Disordersmentioning
confidence: 99%
“…TCF4 transcript levels have been shown to be moderately increased in blood cells of SZ patients and in neurons derived from induced pluripotent stem cells (IPSCs) 17,18 as well as in postmortem brain tissue of SZ patients 19,20 . Moreover, transgenic mice that slightly overexpress a long Tcf4 variant (corresponding to the TCF4B variant as described by Sepp et al 3 in the cortex and hippocampus (Tcf4tg mice) display deficits in sensory gating and impairments in fear-associated learning, attentional dysfunction, and delayed adaptation in a latent inhibition task [21][22][23] . TCF4 is considered a constitutive interaction partner of neuronal bHLH factors and displays pleiotrophic effects 1 and has been shown to be regulated post-trancriptionally by neuronal activity 24 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] According to recent research, the role of TCF4 in central nervous system diseases has become a hot topic receiving general attention, which exerts an important function in the neuronal regulation. [ 38 , 39 ] In the present study, LncRNA GAS5 induced TCF4 protein expression in vitro model by miR-137. Transcription factor TCF4 activates the expression of bHLH.…”
Section: Discussionmentioning
confidence: 59%